Survivors : Storm of Dogs - Book 7 - Hunter, Erin (New York, NY : Harper, an imprint of HarperCollinsPublishers, 2015)
"Lucky and the dogs of the Wild Pack must fight tooth and claw to survive the storm of dogs--the terrifying battle that has been haunting Lucky's dreams"--
Keywords: Dogs -- Juvenile fiction; Wild dogs -- Juvenile fiction; Dogs -- Fiction; Wild dogs -- Fiction; Survival -- Fiction; Adventure and adventurers -- Fiction; Fantasy